Modeling and Forecasting the MarketsVolatility and VaR Dynamics of Commodity - (:unkn) unknown (My University, 2017)
The purpose of this paper is to model and forecast the risk of six commodities namely, crude oil, copper, gold, silver, palladium, and platinum during the period from02/01/2002 to 29/04/2016 using volatility, value at risk and expected shortfall as riskmeasures. After showing that squared returns of all six commodities have a significantlong memory, the volatility, the value at risk and expected shortfall based on fractionalGARCH models are estimated and forecasted. Both forecast performance of volatilitymodels and backtest for value at risk indicate that in many cases FIAPARCH model outperforms the other GARCH models. Then volatility, value at risk and expected shortfallestimates based on FIAPARCH model show that the volatility and market risk of oil ismuch higher than the other commodities. This casts doubt on the use of oil as a hedgingtool.

Bu çalışmanın amacı, ham petrol, bakır, altın, gümüş, paladyum ve platinden oluşan altı temel emtiaya ait zaman serisinin 02/01/2002 - 29/04/2016 arasını kapsayan dönemde, oynaklık, riske maruz değer ve beklenen açık risk ölçümlerini kullanarak, emtia piyasalarının riskini modellemek ve öngörmektir. Bu altı emtianın getiri karelerinin önemli ölçüde uzun hafıza özelliğine sahip olduğu gösterildikten sonra oynaklık, riske maruz değer ve beklenen açık, kesirli bütünleşik GARCH modelleri kullanılarak tahmin edilmiş ve öngörülmüştür. Hem oynaklık modellerinin öngörü performansı hem de riske maruz değer için yapılan geri testler birçok durumda FIAPARCH modelinin diğer GARCH modellerinden bariz biçimde üstün olduğunu göstermektedir. FIAPARCH modelini kullanarak yapılan oynaklık, riske maruz değer ve beklenen açık tahmin sonuçları petrolün diğer emtialardan daha riskli olduğunu göstermekte ve petrolün riskten korunma aracı olarak kullanılmasını sorgulanır hale getirmektedir.
Emtia Piyasalarının Oynaklık ve Riske Maruz Değer Dinamiklerinin Modellenmesi ve Öngörüsü